Social Effects and Leadership in Albania, the Analyze of the Social Influences in Albanian Administrative Developing - Dumi, Alba; Bodo, Eliza; Bega, Elsa; Dupi, Alketa (Mediterranean Journal of Social Sciences, 2012)
This paper identifies and addresses of the important factors underlying of the social and economical influences, the loss of theleadership roles and culturesâ€”the sense of cultural inferiority prevalent among members of community, women, youth, minority groups.The paper also introduces with the leadership styles in Albanian condition and describes the influences of prejudice in this organizationâ€™sefforts to preserve and revitalize the Albanian intangible culture. Prejudice influences convenience or economic reasons. But moreoften, they abandon their culture and language in order to overcome discrimination. Social prejudice reduces quality and slows the flow.Social prejudice is a chasm that separates information from the people who need it. Many leaders are too proud to reach across and askfor it, instead, they will ask someone for their opinion on their side of the chasm. In the technology age, information is needed from thesource, not chain of command or someoneâ€™s theory. To stay competitive, work environments must be free of social prejudice and leadersmust be willing to cross social class barriers to seek information. In the Albania, it is not uncommon for members of dominant cultures, tolook down upon members of a minority cultural group, considering them as â€œsecond classâ€ citizens. Projects are undertaken towardsovercoming the sense of cultural inferiority and instilling cultural pride among the young. In business, social prejudice has always been abarrier to the information. Leadership likes the feeling of its power while the targets of prejudice tolerate it.